Answered

Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Solve the equation
4-t=3(t-1)-5


Sagot :

Tasyha

Answer:

t = 3

Step-by-step explanation:

[tex]4 - t = 3(t - 1) - 5[/tex]

[tex]4 - t = 3t - 3 - 5[/tex]

[tex]4 - t = 3t - 8[/tex]

[tex] - t - 3t = - 8 - 4[/tex]

[tex] - 4t = - 12[/tex]

[tex]t = 3[/tex]